2009
DOI: 10.1007/bf03218903
|View full text |Cite
|
Sign up to set email alerts
|

Polycarprolactone ultrafine fiber membrane fabricated using a charge-reduced electrohydrodynamic process

Abstract: This paper introduces a modified electrospinning system for biomedical wound-healing applications. The conventional electrospinning process requires a grounded electrode on which highly charged electrospun ultrafine fibers are deposited. Biomedical wound-healing membranes, however, require a very low charge and a low level of remnant solvent on the electrospun membrane, which the conventional process cannot provide. An electrohydrodynamic process complemented with field-controllable electrodes (an auxiliary el… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 14 publications
2
1
0
Order By: Relevance
“…Further, Kim et al. reported that the fibrous membranes with a pore size in the range of 500–1000 nm showed better protection against the bacteria [31]. Our pore size of the fabricated composite was observed to be within this range suggesting it as a potential membrane for protection against the bacterial invasion.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…Further, Kim et al. reported that the fibrous membranes with a pore size in the range of 500–1000 nm showed better protection against the bacteria [31]. Our pore size of the fabricated composite was observed to be within this range suggesting it as a potential membrane for protection against the bacterial invasion.…”
Section: Resultssupporting
confidence: 54%
“…Further, they suggested that the reason for the reduction in the pore size was due to the smaller fiber diameter exhibited by the fabricated membranes [30] which is similar to our observations. Further, Kim et al reported that the fibrous membranes with a pore size in the range of 500-1000 nm showed better protection against the bacteria [31]. Our pore size of the fabricated composite was observed to be within this range suggesting it as a potential membrane for protection against the bacterial invasion.…”
Section: Pore Size Investigationsupporting
confidence: 58%
“…Kim et al [22] examined the usage of auxiliary electrodes of varying dimensions in order to determine the electric field concentration and the effect of the electric field at the nozzle tip. According to Kim et al [23], a slightly modified electrospinning technique included an extra electrode, an air blowing system, and a guiding electrode.…”
Section: Introductionmentioning
confidence: 99%